Double-layer carbon-coated hydrogen storage alloy as well as preparation method and application thereof
By forming a double-layer carbon cladding on the surface of A2B7 La-Y-Ni-based rare earth hydrogen storage alloy, the problem of poor oxidation resistance and cycling performance is solved, and higher electrochemical performance and cycling stability is achieved. It is suitable for negative electrode materials for nickel-hydrogen batteries.
Patent Information
- Application Number
- CN202411898049.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The existing A2B7 La-Y-Ni-based rare earth hydrogen storage alloy materials have problems such as poor oxidation resistance and poor circulation and rate performance in nickel-hydrogen batteries, which limits their practical application.
Using the double-layer carbon coating technology, the hydrogen storage alloy is dispersed into the aqueous trimethylolamide aqueous solution, dopamine hydrochloride is added and polydopamine coated, and then heat treatment is carried out under an argon/acetylene atmosphere to form a double-layer carbon coating layer of polydopamine pyrolyzed carbon and carbon nanotubes.
It significantly improves the antioxidant capacity of hydrogen storage alloys, extends the service life of the material, optimizes performance, improves cycle stability, and is simple to operate, making it easy to promote and apply.
Smart Images

Figure CN119703066A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a double-layer carbon-coated hydrogen storage alloy and a preparation method and application thereof, belonging to the technical field of hydrogen storage alloy negative electrode for nickel-hydrogen battery and preparation thereof. Background Art
[0002] Hydrogen storage alloys are widely used in the fields of nickel-hydrogen battery negative electrode materials, hydrogen compression, solid-state hydrogen storage, heat storage, etc. due to their high safety and good reversibility of hydrogen absorption and desorption. They are important functional materials in the field of hydrogen energy development and application. As a negative electrode material for nickel-hydrogen batteries, they have the advantages of excellent wide temperature performance, good kinetic performance, environmental friendliness, and high safety. They are widely used in electric vehicles, large-scale energy storage, coal mine lighting, ice and snow industry, etc.
[0003] The hydrogen storage alloys that can be used as negative electrodes for nickel-hydrogen batteries mainly include AB5, A2B, AB2, A2B7 and vanadium-based solid solutions. Since A2B, AB2 and vanadium-based solid solutions have difficulty absorbing and releasing hydrogen at room temperature, they cannot be used in the battery field. LaNi5 hydrogen storage alloys are the main negative electrode materials for nickel-hydrogen batteries because of their long cycle life, mature technology and environmental friendliness. However, the maximum discharge capacity of commercial LaNi5 hydrogen storage alloys is 350mAh / g, which is close to the theoretical value (372mAh·g -1 ), and it also has problems such as poor high-rate discharge performance and high cost. Therefore, the development of new hydrogen storage alloys is crucial for the development of high-energy-density nickel-hydrogen batteries.
[0004] In recent years, high-capacity A2B7 type La-Y-Ni based rare earth hydrogen storage alloy materials have attracted extensive attention from scientific researchers, but their poor antioxidant properties have resulted in poor cycle performance and rate performance, which has severely limited their practical applications. Studies have shown that the surface composition, microstructure and electrocatalytic activity of the alloy have an important influence on the performance of nickel-hydrogen batteries. Therefore, in the prior art, surface coating modification treatment is often used to change the surface properties of the alloy, improve the electrode performance of the alloy, and accelerate its promotion and application process.
[0005] Existing studies have shown that surface modification of hydrogen storage alloy electrode materials is an effective solution to improve the performance of the negative electrode of nickel-hydrogen batteries. This solution effectively changes the surface state of the hydrogen storage alloy while ensuring that the overall properties of the original hydrogen storage alloy remain unchanged, thereby improving the electrochemical and kinetic properties of the hydrogen storage alloy. Commonly used alloy surface modification methods include: surface coating metal film treatment, alkaline and acidic solution treatment, surface polymer modification and other methods. Among them, the surface coating metal film treatment is easy to fall off due to the lack of symbiotic phase between the coating layer and the alloy, resulting in failure. Alkaline and acidic solution treatment often causes excessive corrosion of the alloy, loss of effective capacity, and reduced cycle stability. Another way of surface polymer modification can form microspaces on its surface. By selecting different surface groups, the diffusion of H2 can be regulated, the material can be prevented from falling off, the utilization rate can be improved, and the cycle stability of the negative electrode material of nickel-hydrogen batteries can be improved, thereby achieving the goal of its commercial application. The current patents mainly focus on the optimization of alloy material composition, and only a few studies are aimed at alloy surface coating. For example, patent CN110835091A uses reflux, calcination, ball milling and other methods to load Zr-based MOFs on the surface of PAN-based porous carbon-magnesium alloy materials. Based on this, without changing the existing A2B7 type La-Y-Ni based rare earth hydrogen storage alloy material production process and equipment, the development of a new surface coating modification method has important application significance. It is convenient for large-scale production and greatly improves the electrochemical properties of A2B7 type La-Y-Ni based rare earth hydrogen storage alloy materials, which can well meet the needs of current social development. Summary of the invention
[0006] In order to solve the above problems existing when the existing A2B7 type La-Y-Ni based rare earth hydrogen storage alloy material is used as a hydrogen storage alloy negative electrode for nickel-hydrogen batteries, the present invention provides a double-layer carbon-coated hydrogen storage alloy and a preparation method and application thereof.
[0007] The technical solution of the present invention:
[0008] One of the purposes of the present invention is to provide a method for preparing a double-layer carbon-coated hydrogen storage alloy, the method comprising the following steps:
[0009] (1) dispersing the hydrogen storage alloy into a tris(hydroxymethyl)aminomethane aqueous solution and stirring the mixture to obtain a mixed solution;
[0010] (2) adding dopamine hydrochloride to the mixed solution, stirring and then allowing to stand to obtain a mixed turbid solution;
[0011] (3) centrifuging, washing, and vacuum drying the mixed turbid liquid to obtain a polydopamine-coated hydrogen storage alloy;
[0012] (4) The polydopamine-coated hydrogen storage alloy is heat-treated in an argon / acetylene mixed atmosphere to obtain a double-layer carbon-coated hydrogen storage alloy.
[0013] It is further defined that the hydrogen storage alloy in (1) is an A2B7 type La-Y-Ni based rare earth hydrogen storage alloy with a particle size of 200-400 mesh.
[0014] Further defined, the hydrogen storage alloy is LaY2Ni 9.5 Mn 0.5 Al 0.5 .
[0015] It is further defined that the mass volume ratio of the hydrogen storage alloy and the tris(hydroxymethyl)aminomethane aqueous solution in (1) is 0.5-3 g:100 mL, the mass concentration of the tris(hydroxymethyl)aminomethane aqueous solution is 0.01-1 mol / L, and the pH value is 8.0-10.5.
[0016] It is further defined that the mass ratio of dopamine hydrochloride to the hydrogen storage alloy in the mixed turbid liquid of (2) is 0.1-0.6:1-3.
[0017] It is further defined that the stirring time in (2) is 6 to 48 hours, and the standing time is 5 to 10 minutes.
[0018] It is further specified that in (3), deionized water and anhydrous ethanol are used as detergents.
[0019] It is further defined that the vacuum drying temperature in (3) is 40 to 60° C. and the time is 5 to 15 hours.
[0020] It is further defined that the volume ratio of argon to acetylene in the argon / acetylene gas mixture in (4) is 85-95:5-15.
[0021] It is further defined that the heat treatment temperature in (4) is 450-500°C, the time is 30-60 min, and the heating rate is 2-5°C min -1 .
[0022] The second object of the present invention is to provide a double-layer carbon-coated hydrogen storage alloy prepared by the above method.
[0023] The third object of the present invention is to provide an application of the above-mentioned double-layer carbon-coated hydrogen storage alloy, specifically as a hydrogen storage alloy negative electrode for nickel-hydrogen batteries.
[0024] Beneficial effects of the present invention:
[0025] The present invention firstly uniformly coats the surface of a rare earth hydrogen storage alloy with a polydopamine carbon layer, and then utilizes the catalytic effect of the rare earth hydrogen storage alloy to catalyze acetylene at high temperature into carbon nanotubes attached to the surface of the rare earth hydrogen storage alloy not coated with polydopamine and the surface of the polydopamine carbon layer, thereby obtaining a rare earth hydrogen storage alloy negative electrode for a nickel-hydrogen battery coated with polydopamine pyrolytic carbon and a double-layer carbon of carbon nanotubes. The modification method of the rare earth hydrogen storage alloy provided by the present invention can improve the oxidation resistance of the alloy surface, effectively alleviate the pulverization of the material, and extend the service life of the alloy. At the same time, utilizing the advantages of large specific surface area and adjustable pore size of polydopamine pyrolytic carbon and carbon nanotube double carbon layers, the performance of the rare earth hydrogen storage alloy can be optimized and the cycle stability can be improved. In addition, the modification method of the rare earth hydrogen storage alloy provided by the present invention is simple and easy to operate, and is convenient for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 for LaY2Ni 9.5 Mn 0.5 Al 0.5 SEM images of rare earth hydrogen storage alloys;
[0027] Figure 2 The LaY2Ni prepared in Comparative Example 1 9.5 Mn 0.5 Al 0.5 @SEM photo of PDA rare earth hydrogen storage alloy;
[0028] Figure 3 The LaY2Ni prepared in Example 1 9.5 Mn 0.5 Al 0.5 SEM photo of @PDA@CNT rare earth hydrogen storage alloy;
[0029] Figure 4 This is a comparison chart of the electrochemical performance of the negative electrodes prepared in Comparative Example 1 and Example 1. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0032] Comparative Example 1
[0033] (1) LaY2Ni 9.5 Mn0.5 Al 0.5 The rare earth hydrogen storage alloy material is fully ground and sieved in a mortar to select alloy powder with a particle size of 200-400 meshes.
[0034] (2) Weigh 2g LaY2Ni 9.5 Mn 0.5 Al 0.5 The rare earth hydrogen storage alloy material and 0.5 g dopamine hydrochloride were dissolved in 100 mL of 0.1 mol / L tris(hydroxymethyl)aminomethane) aqueous solution, stirred for 24 h to obtain a mixed solution, allowed to stand for 5 min and then centrifuged, washed three times with deionized water and anhydrous ethanol, and placed in a vacuum drying oven at 60 °C for 12 h to obtain LaY2Ni coated with polydopamine. 9.5 Mn 0.5 Al 0.5 Rare earth hydrogen storage alloy materials.
[0035] (3) The obtained LaY2Ni coated with polydopamine 9.5 Mn 0.5 Al 0.5 The rare earth hydrogen storage alloy material was placed in a tubular furnace filled with argon atmosphere for heat treatment, wherein the heating rate was 3°C / min, the heating temperature was 500°C, and the holding time was 60min. Finally, the polydopamine pyrolysis carbon-coated rare earth hydrogen storage alloy negative electrode material for nickel-hydrogen battery was obtained, named LaY2Ni 9.5 Mn 0.5 Al 0.5 @PDA.
[0036] (4) LaY2Ni 9.5 Mn 0.5 Al 0.5 @PDA and carbonyl nickel powder were mixed in a mass ratio of 1:4 and pressed into tablets at 15MPa. The tabs were then wrapped with nickel foam and welded to obtain a negative electrode with an active material loading of approximately 100mg.
[0037] Example 1
[0038] (1) LaY2Ni 9.5 Mn 0.5 Al 0.5 The rare earth hydrogen storage alloy material is fully ground and sieved in a mortar to select alloy powder with a particle size of 200-400 meshes.
[0039] (2) Weigh 2g LaY2Ni 9.5 Mn 0.5 Al 0.5The rare earth hydrogen storage alloy material and 0.5 g dopamine hydrochloride were dissolved in 100 mL of 0.1 mol / L tris(hydroxymethyl)aminomethane) aqueous solution, stirred for 24 h to obtain a mixed solution, allowed to stand for 5 min and then centrifuged, washed three times with deionized water and anhydrous ethanol, and placed in a vacuum drying oven at 60 °C for 12 h to obtain LaY2Ni coated with polydopamine. 9.5 Mn 0.5 Al 0.5 Rare earth hydrogen storage alloy materials.
[0040] (3) LaY2Ni coated with polydopamine 9.5 Mn 0.5 Al 0.5 The rare earth hydrogen storage alloy material was placed in a tubular furnace filled with argon / acetylene (95% Ar / 5% C2H2) mixed gas atmosphere for heat treatment, wherein the heating rate was 3°C / min, the heating temperature was 500°C, and the holding time was 60min. Finally, the rare earth hydrogen storage alloy negative electrode material for nickel-hydrogen battery coated with polydopamine pyrolytic carbon and carbon nanotube double-layer carbon was obtained, named LaY2Ni 9.5 Mn 0.5 Al 0.5 @PDA@CNT.
[0041] (4) LaY2Ni 9.5 Mn 0.5 Al 0.5 @PDA@CNT and carbonyl nickel powder were mixed in a mass ratio of 1:4 and pressed into tablets under 15MPa. The tabs were then wrapped with nickel foam and welded to obtain a negative electrode with an active material loading of approximately 100mg.
[0042] Effect example
[0043] (1) LaY2Ni 9.5 Mn 0.5 Al 0.5 Rare earth hydrogen storage alloy and LaY2Ni prepared in Comparative Example 1 and Example 1 9.5 Mn 0.5 Al 0.5 @PDA and LaY2Ni 9.5 Mn 0.5 Al 0.5 The surface microstructure of @PDA@CNT was characterized, and the results were as follows: Figures 1 to 3 As shown in the figure, LaY2Ni 9.5 Mn 0.5 Al 0.5 The surface of rare earth hydrogen storage alloy is relatively smooth. 9.5 Mn 0.5 Al 0.5The surface of PDA has a uniform wrinkled structure, indicating that its surface is uniformly coated with polydopamine pyrolytic carbon. 9.5 Mn 0.5 Al 0.5 In addition to the uniform wrinkled structure, the surface of @PDA@CNT also has a carbon nanotube structure, that is, 9.5 Mn 0.5 Al 0.5 The surface of the rare earth hydrogen storage alloy is uniformly coated with a double-layer carbon structure of polydopamine pyrolytic carbon and carbon nanotubes.
[0044] (2) LaY2Ni 9.5 Mn 0.5 Al 0.5 and carbonyl nickel powder in a mass ratio of 1:4, and pressed under 15MPa, and then welded to the tabs after wrapping with nickel foam to obtain a negative electrode with an active material loading of about 100mg. The negative electrode and the negative electrode prepared in Comparative Example 1 and Example 1 were used to prepare a negative electrode battery. The positive electrode used sintered α-nickel hydroxide, a sulfonated polypropylene grafted membrane was used as a diaphragm, the electrolyte was 6M KOH solution, and the electrochemical performance was tested in the voltage range of 0.8-1.6V. The activation performance at 0.2C rate and the discharge cycle performance at 1C rate are shown in Figure 2. Figure 4 As shown in the figure, La Y2Ni 9.5 Mn 0.5 Al 0.5 、LaY2Ni 9.5 Mn 0.5 Al 0.5 @PDA, LaY2Ni 9.5 Mn 0.5 Al 0.5 The maximum discharge capacity of @PDA@CNT rare earth hydrogen storage alloy materials at 0.2C rate is 381mAh·g -1 、362mAh·g -1 and 348mAh g -1 After 100 cycles, LaY2Ni 9.5 Mn 0.5 Al 0.5 、LaY2Ni 9.5 Mn 0.5 Al 0.5 @PDA and LaY2Ni 9.5 Mn 0.5 Al 0.5 The maximum discharge capacity of @PDA@CNT rare earth hydrogen storage alloy materials at 0.5C rate is 198 mAh g -1 , 254mAh·g -1 and 280.5mAh g -1 .
[0045] In summary, carbon-coated LaY2Ni 9.5 Mn 0.5 Al 0.5 The cyclic stability of rare earth hydrogen storage alloy materials is significantly better than that of LaY2Ni without carbon coating. 9.5 Mn 0.5 Al 0.5 Rare earth hydrogen storage alloy materials, which fully proves that carbon coating plays a good role in stabilizing LaY2Ni 9.5 Mn 0.5 Al 0.5 The surface structure of rare earth hydrogen storage alloy materials effectively prevents material pulverization and electrolyte corrosion, thereby greatly improving the cycle performance under high current density, and has more advantages in commercial promotion. 9.5 Mn 0.5 Al 0.5 The discharge capacity of @PDA@CNT is significantly better than that of LaY2Ni coated with single-layer carbon. 9.5 Mn 0.5 Al 0.5 @PDA.
[0046] The above description is only a preferred embodiment of the present invention. In view of the fact that technicians in the field of the present invention can make appropriate changes and modifications to the above implementation, the present invention is not limited to the specific implementation described above. Some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a double-layer carbon-coated hydrogen storage alloy, characterized in that: include: (1) dispersing the hydrogen storage alloy into a tris(hydroxymethyl)aminomethane aqueous solution and stirring the mixture to obtain a mixed solution; (2) adding dopamine hydrochloride to the mixed solution, stirring and then allowing to stand to obtain a mixed turbid solution; (3) centrifuging, washing, and vacuum drying the mixed turbid liquid to obtain a polydopamine-coated hydrogen storage alloy; (4) The polydopamine-coated hydrogen storage alloy is heat-treated in an argon / acetylene mixed atmosphere to obtain a double-layer carbon-coated hydrogen storage alloy.
2. The preparation method according to claim 1, characterized in that: (1) The medium hydrogen storage alloy is an A2B7 type La-Y-Ni based rare earth hydrogen storage alloy with a particle size of 200-400 mesh.
3. The preparation method according to claim 1, characterized in that: (1) The mass volume ratio of the hydrogen storage alloy to the tris(hydroxymethyl)aminomethane aqueous solution is 0.5-3 g:100 mL, the mass concentration of the tris(hydroxymethyl)aminomethane aqueous solution is 0.01-1 mol / L, and the pH value is 8.0-10.
5.
4. The preparation method according to claim 1, characterized in that: The mass ratio of dopamine hydrochloride to the hydrogen storage alloy in the mixed turbid solution of (2) is 0.1-0.6:1-3.
5. The preparation method according to claim 1, characterized in that: (2) The stirring time is 6 to 48 hours and the standing time is 5 to 10 minutes.
6. The preparation method according to claim 1, characterized in that: (3) Deionized water and anhydrous ethanol are used as detergents; the vacuum drying temperature is 40 to 60°C and the time is 5 to 15 hours.
7. The preparation method according to claim 1, characterized in that: (4) The volume ratio of argon to acetylene in the argon / acetylene mixture is 85-95:5-15.
8. The preparation method according to claim 1, characterized in that: (4) The heat treatment temperature is 450-500°C, the time is 30-60 min, and the heating rate is 2-5°C min -1 .
9. A double-layer carbon-coated hydrogen storage alloy prepared by the method according to any one of claims 1 to 8.
10. An application of the double-layer carbon-coated hydrogen storage alloy according to claim 9, characterized in that: Used as hydrogen storage alloy negative electrode for nickel-hydrogen batteries.
Citation Information
Patent Citations
Preparation method of dopamine-coated carbon nanotube-modified carbon fiber-enhanced resin base structure-damping composite material
CN109181228A
High-specific-capacity lithium iron phosphate electrode material and preparation method thereof
CN113213448A
Coating method of rare earth hydrogen storage alloy powder for negative electrode for carbon nanotube coated nickel-hydrogen battery
CN114029481A
Molybdenum diselenide / carbon electrode material and preparation method and normal / low temperature application thereof
CN116632195A
Information processing apparatus, method of controlling information processing apparatus, and non-transitory computer-readable storage medium
KR1020200115183A